Effect of auditor's role conflict on auditor’s stress with core self-evaluations as moderators - Putra, I Gede Bandar Wira; Sudana, I Putu (International research journal of management, IT and social sciences, 2019)
The purpose of this study was to provide empirical evidence of the effect of core self-evaluations on the relationship between auditor's role conflict and auditor’s stress. 82 auditors who work in a Public Accountant Office registered in the Province of Bali are used as a population by using purposive sampling in accordance with established criteria. The data analysis technique used was moderated regression analysis. The results showed that auditor’s role conflict had a positive effect on auditor’s stress and showed that core self-evaluations weakened the influence of auditor’s role conflict on auditor’s stress. The results of this study can be taken into consideration for the Public Accountant Firm to use personality tests in the auditor's career selection and development process and provide empirical evidence for the model of stress theory.